Study on Fe-C-Al three-phase micro-electrolysis treatment of low concentration phosphorus wastewater - Hu, Baoming; Qi, Quan; Li, Liang; Huan, Yongzhao; Liu, Zheng; Liu, Xuqing (Water science and technology, 2022)
In this study, the iron-carbon-aluminum (Fe-C-Al) composite filler was prepared by aluminum modification of conventional iron-carbon (Fe-C) micro-electrolysis with a no-burn method. The optimal process conditions for Fe-C-Al three-phase micro-electrolysis treatment of low concentration phosphorus wastewater were determined to be the aluminum metal ratio of 14 wt% and solids dosing of 30 g/L. Under the optimal process conditions, Fe-C-Al three-phase micro-electrolysis was performed for the treatment of low concentration phosphorus wastewater (LCPW) with continuous experiment, while iron-carbon fillers before and after treatment were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results showed that the amount of Fe2+ dissolved in the micro-electrolysis determined the micro-electrolysis phosphorus removal effect, Al promoted the dissolution of Fe2+, and the Fe-C-Al filler had a stable phosphorus removal effect, and the average removal efficiency of phosphorus was 67.40%, which is an average improvement of 29.25% compared with the conventional Fe-C filler. The treatment of LCPW by Fe-C-Al three-phase micro-electrolysis is consistent with a first-order kinetic reaction with apparent activation energy of 38.70 kJ·mol−1, which is controlled by the chemical reaction.